Produção de biossurfactantes a partir de resíduos da indústria de laticínios para aplicação em processos de biorremediação - Decesaro, Andressa (2016)
The production of biosurfactants using agroindustrail wastes has been the focus of several studies, given the need to reduce the cost of production of these biocompounds. Biosurfactants can be can be applied in numerous industrial sectors, and in bioremediation processes, wherein the compound permits desorption and the resulting contaminant emulsion, thereby facilitating the assimilation by the indigenous microorganisms, resulting in the remediation of the contaminated soil. The aim of this study was to produce biosurfactants and use these biocompounds in bioremediation of ex situ soil contaminated with biodiesel. The biosurfactants were produced by bacteria Bacillus methylotrophicus and Bacillus pumilus, previously isolated from soil contaminated with diesel oil. The production of biosurfactantswas accomplished using submerged fermentation in a culture media added by whey or permeate of whey ultrafiltration, supplemented with nitrogen sources, micronutrients and inducers. After, biosurfactants was obtained from the fermentation media and used in an experimental design with the aim of evaluate the influence of the addition of biosurfactants in the bioremediation of a soil contaminated with biodiesel. The biosurfactant produced proved suitable for the reduction of surface tension, with the lowest surface tension value obtained in the media prepared with addition of ammonium sulfate at a concentration of 1.0% with micronutrients and soybean oil as an inducer at a concentration of 2.0% for both microorganisms. The minimal superficial tension, to fermentation with whey, was obtained with Bacillus methylotrophicus (27.51 mN/m) and in the fermentation realized using the permeate from ultrafiltration whey the superficial tension was 26.02 mN/m using the Bacillus pumilus). Both microorganisms showed behavioral stability, because the re-treatment with further reduction of tension superficial yielded very similar results to those achieved in the implementation of the experimental desing. The biosurfactant produced showed potential for use in bioremediation of soil contaminated with biodiesel, wherein the maximum removal of about 57% was obtained in assays performed with biosurfactant added at a concentration of 0.5% and 1.0% in soil does not sterilized after 90 d test. Regarding treatments with sterile soil, the removal of the contaminant was around 20%, indicating that the percentage of biosurfactant not influenced. This percentage is due to the contaminant adhesion in the soil matrix, it is not possible removal by methods and solvents. The release of CO2, showed high levels of carbon accumulated in the tests added biosurfactant, the maximum value of 6474.41 mg C-CO2/kg soil, with 0.5% of biosurfactant. Thus, it was found that the use of biosurfactants in concentrations of 0.1% to 1.0% assisted in the removal of soil biodiesel without influence on the physico-chemical processes of the contaminant in the soil.